Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine the values of [tex]\( h \)[/tex] at specific points, we need to evaluate the piecewise function at those points by choosing the appropriate cases.
Step-by-Step Solution:
1. Evaluate [tex]\( h(0) \)[/tex]:
- For [tex]\( x = 0 \)[/tex], we look at the piecewise function's domain definitions:
- Since [tex]\( -2 \leq 0 \leq 1 \)[/tex], use the second case: [tex]\( h(x) = (x - 1)^2 - 2 \)[/tex].
- Plug [tex]\( x = 0 \)[/tex] into the equation:
[tex]\[ h(0) = (0 - 1)^2 - 2 = (-1)^2 - 2 = 1 - 2 = -1 \][/tex]
- Therefore, [tex]\( h(0) = -1 \)[/tex].
2. Evaluate [tex]\( h(1) \)[/tex]:
- For [tex]\( x = 1 \)[/tex], again we check the domain definitions:
- Since [tex]\( -2 \leq 1 \leq 1 \)[/tex], use the second case: [tex]\( h(x) = (x - 1)^2 - 2 \)[/tex].
- Plug [tex]\( x = 1 \)[/tex] into the equation:
[tex]\[ h(1) = (1 - 1)^2 - 2 = 0^2 - 2 = 0 - 2 = -2 \][/tex]
- Therefore, [tex]\( h(1) = -2 \)[/tex].
3. Evaluate [tex]\( h(3) \)[/tex]:
- For [tex]\( x = 3 \)[/tex], check the domain definitions:
- Since [tex]\( 3 > 1 \)[/tex], use the third case: [tex]\( h(x) = 2 \)[/tex].
- Therefore, [tex]\( h(3) = 2 \)[/tex].
The final values for the function at the given points are:
[tex]\[ \begin{array}{l} h(0) = -1 \\ h(1) = -2 \\ h(3) = 2 \end{array} \][/tex]
Step-by-Step Solution:
1. Evaluate [tex]\( h(0) \)[/tex]:
- For [tex]\( x = 0 \)[/tex], we look at the piecewise function's domain definitions:
- Since [tex]\( -2 \leq 0 \leq 1 \)[/tex], use the second case: [tex]\( h(x) = (x - 1)^2 - 2 \)[/tex].
- Plug [tex]\( x = 0 \)[/tex] into the equation:
[tex]\[ h(0) = (0 - 1)^2 - 2 = (-1)^2 - 2 = 1 - 2 = -1 \][/tex]
- Therefore, [tex]\( h(0) = -1 \)[/tex].
2. Evaluate [tex]\( h(1) \)[/tex]:
- For [tex]\( x = 1 \)[/tex], again we check the domain definitions:
- Since [tex]\( -2 \leq 1 \leq 1 \)[/tex], use the second case: [tex]\( h(x) = (x - 1)^2 - 2 \)[/tex].
- Plug [tex]\( x = 1 \)[/tex] into the equation:
[tex]\[ h(1) = (1 - 1)^2 - 2 = 0^2 - 2 = 0 - 2 = -2 \][/tex]
- Therefore, [tex]\( h(1) = -2 \)[/tex].
3. Evaluate [tex]\( h(3) \)[/tex]:
- For [tex]\( x = 3 \)[/tex], check the domain definitions:
- Since [tex]\( 3 > 1 \)[/tex], use the third case: [tex]\( h(x) = 2 \)[/tex].
- Therefore, [tex]\( h(3) = 2 \)[/tex].
The final values for the function at the given points are:
[tex]\[ \begin{array}{l} h(0) = -1 \\ h(1) = -2 \\ h(3) = 2 \end{array} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.